(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Analysis of cephalometric films plays an important role in diagnosis and treatment planning. Film measurements were used to classify malocclusion and to compare post-treatment change. Objective: To evaluate the results of hard and soft tissue changes after treatment of Class II Angle malocclusion with the MBT bracket system at the Department of Odonto-Stomatology, Can Tho University of Medicine and Pharmacy. Materials and methods: The study was conducted on 31 patients with Class II Angle malocclusion at the Department of Odonto-Stomatology, Can Tho University of Medicine and Pharmacy. Conduct orthopedic treatment of class II Angle malocclusion. Evaluation of changes in bones, teeth, and soft tissue on cephalometric radiographs and all X-ray films will be analyzed by specialized software with copyright V-ceph 6.0. Compare the indicators on the film before and after treatment. Results: The index of the angle SNA, ANB, OP-SN, and SN-GoGn changed before and after treatment, with statistical significance (p<0.05). The change in SNB angle after treatment was not statistically significant. However, the difference in dental measurements was statistically significant (p<0.05). Compared with the S aesthetic line, the protrusion of the upper lip and the lower lip decreased respectively by 1.10 ± 0.72mm and 0.68 ±1.06mm.